The International Biogeography Society: enabling a dynamic discipline - Rosemary G. Gillespie (Frontiers of Biogeography)
Biogeography is a dynamic field that has transformed dramatically over the last few decades from being necessarily descriptive to become a rigorous science. Major recent areas of growth have included phylogenetics and phylogeography, microbial biogeography and metagenomics, and macroecology. However, the welcome recent deluge of massive amounts of data, in particular from genomics, museum specimens, and field observations, as well as environmental information, is posing a huge challenge to the field. The society has several key roles, not only to serve as a home for researchers in the field and enabling interaction among them, but also: (1) to provide a forum to facilitate awareness and use of rapidly developing tools and data; (2) to encourage a solid foundation in organismal research, with emphasis on field and museum based resources; (3) to promote global connections; and (4) to cultivate interdisciplinarity, such that the predictive capabilities of the field can be used to inform management and policy.